O silêncio e o sofrimento/adoecimento psíquico docente sob a análise da Psicologia Histórico-Cultural: das condições às emoções - Freire, Silvia Segovia Araujo (2023)
In carrying out their activity, human beings involve their desires, expectations, feelings and emotions, and the way in which they organize and control them will directly contribute to their performance in the face of different situations in the work environment. Based on this understanding, this research had as its main objective to analyze the causes of suffering/psychic illness of teachers from the municipal education network in the municipality of Corumbá - Mato Grosso do Sul from the perspective of Historical-Cultural Psychology (PHC) The choice for this The theoretical approach made it possible to understand phenomena such as psychic suffering/illness and its scope based on questions that encompass human activity and its concrete and historically constituted dimensions. This is qualitative research that used the following instruments as methodological procedures: a questionnaire with five research items and two scales, the Stress Questionnaire for Teachers: Basic and Secondary Education (QSPEBS) and the Self-Reporting Questionnaire (SRQ-20), applied in the same form to teachers through the online platform. For the managers, a questionnaire was applied with the objective of investigating the existence of action, project or coping program and the conception of the teaching psychic suffering/illness with the purpose of complementing the teachers' speeches. The questionnaire was applied to the teachers who were in the classroom, and in the total of 984 questionnaires applied, we reached 118 (12%) answers, and in relation to the managers, out of 251 participants, we reached 26 answers (10.35%). In all, among participating teachers and administrators, we obtained 144 responses. Due to the pandemic, the instruments were applied through an online platform organized in Google Forms. The collected information was organized in tables and the answers presented by frequency. For the analysis and discussion process, we considered the first four responses with the highest frequencies in each table. The results revealed similarities and disparities in the responses of teachers and managers, but pointed out that interpersonal relationships, working conditions, unexpected situations such as the pandemic, availability and training for the use of technological resources, the lack of a healthy environment and listening qualified and the absence of actions, projects, programs to equip teachers to manage or minimize psychological suffering/illness are aspects considered important for teachers and administrators. Managers identified the absence or precariousness of action, projects or programs to prevent teacher suffering/psychic illness. Both teachers and managers who participated in the survey point out that issues related to mental health, psychological care, collective or individual, healthy work environments, more and better training and aspects related to working conditions are important topics for future projects aimed at coping with the teaching psychological suffering/illness. It was evidenced in this research that the social conditions resulting from the materiality of capitalist society result in the devaluation and lack of prestige of teaching work, in inadequate conditions and work overload, and therefore lead to the compromise of interpersonal relationships and the silencing of teachers' emotions, providing opportunities for psychic suffering/illness.